Prolonged Periods of Social Isolation From Weaning Reduce the Anti-inflammatory Cytokine IL-10 in Blood and Brain - Corsi-Zuelli, Fabiana; Fachim, Helene Aparecida; Loureiro, Camila Marcelino; Shuhama, Rosana; Bertozi, Giuliana; Joca, Sâmia Regiane Lourenço; Menezes, Paulo Rossi; Louzada-Junior, Paulo; Del-Ben, Cristina Marta (Frontiers in Neuroscience, 2019)
Life stressors during critical periods are reported to trigger an immune dysfunction characterised by abnormal production of inflammatory cytokines. Despite the relationship between early stressors and schizophrenia is described, the evidence on inflammatory biomarkers remains limited. We aimed to investigate whether an imbalance between pro- and anti-inflammatory cytokines in the brain is reflected in the peripheral blood of rats submitted to post-weaning social isolation (pwSI), a model with validity to study schizophrenia. We evaluated pro- and anti-inflammatory cytokines (IL-6, TNF-α, IL-10) simultaneously at blood, prefrontal cortex and hippocampal tissues (Milliplex MAP; pg/mL), including the respective cytokines gene expression (mRNA) (qRT-PCR TaqMan mastermix). We also investigated whether abnormal cytokine production would correlate with hyperlocomotion in social isolated-animals. Male Wistar rats (n = 10/group) were kept isolated (n = 1/cage) or grouped (n = 3-4/cage) since weaning for 10 weeks. After this period, rats were assessed for locomotion and sacrificed for blood and brain cytokines measurements. Prolonged pwSI decreased IL-10 protein and mRNA in the blood, and IL-10 protein in the hippocampus, along with decreased IL-6 and its mRNA expression in the prefrontal cortex. IL-10 hippocampal levels were negatively correlated with hyperlocomotion in the open field. Although the unexpected decrease in IL-6 and unchanged TNF-α levels contrast to the expected pro-inflammatory phenotype, this may suggest that reduced anti-inflammatory signalling may be critical for eliciting abnormal behaviour in adulthood. Altogether, these results suggest that prolonged early-life adverse events reduce the ability to build proper anti-inflammatory cytokine that is translated from blood-to-brain.